PENGARUH PEMBERIAN BUAH PEPAYA CALINA TERHADAP KELANCARAN ASI PADA IBU MENYUSUI DI WILAYAH KERJA UPT PUSKESMAS LUBUK MUDA KABUPATEN BENGKALIS - Susiyami Susiyami; Wira Ekdeni Aifa; Fajar Sari Tanberika; Rizka Mardiya (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Breastfeeding is the best method of feeding infants. The coverage of exclusive breastfeeding in the working area of the UPT Lubuk Muda Health Center is below the target, this can be caused by insufficient breast milk production. Lactagogum is a substance that can increase breast milk production, which is found in papaya fruit. The purpose of this study was to determine the effect of giving Calina papaya fruit on the smoothness of breast milk in breastfeeding mothers in the working area of the UPT Lubuk Muda Health Center. The type of research used in this study is experimental research. The research design is quasi-experimental and one group pre-test and post-test design using a comparison group. The population is 30 breastfeeding mothers with a sample size of 24 people. Respondents are divided into two groups, 12 respondents in the treatment group and 12 respondents in the control group. The sampling technique uses purposive sampling. Data analysis is bivariate analysis using a paired t-test. The amount of breast milk before being given Calina papaya fruit in the intervention group averaged 176.67 cc. Meanwhile, the control group averaged 181.25 cc. The amount of breast milk after being given papaya in the intervention group on the first day was 179.17 cc on average. Meanwhile, the control group averaged 181.25 cc on the first day. There was an effect of giving Calina papaya on the smooth flow of breast milk in breastfeeding mothers (p-value 0.011 0.05). Research conclusion: There is an effect of giving papaya calina fruit on the smoothness of breast milk in breastfeeding mothers in the Working Area of the UPT Lubuk Muda Health Center. The output of the research is a Journal. It is hoped that breastfeeding mothers should regularly consume papaya calina fruit because giving papaya fruit to breastfeeding mothers can stimulate the increase in secretion and the amount of breast milk production.Keywords : Papaya fruit, Smooth breast milk flow